Exploring the Basic Needs of Street Children in Pabna Municipality - Islam, Md. Sefatul; Makhon , Md. Lutfur Rahman (Papanda Publisher, 2025)
The objective of the study explores the impact of residence and education status on the basic needs of street children in Pabna Municipality, Bangladesh. In contrast, the goal of this study is to discuss the level of education attained and residence consciousness of street children residing in the Pabna Municipality. The research was carried out by quantitative method using a convenient sampling technique, in which 88 children living on the streets from various Pabna Municipality areas took part in total. The socioeconomic status of the street children in Pabna Municipality is shown by the study, as is the situation of deprivation concerning their place of residence and level of education. Our findings designate a strong correlation between the lack of stable residence and poor access to education and the heightened vulnerability of these children to meeting their basic needs. The main reasons respondents don't go to school and live in unsanitary areas like slums, stations, and markets are poverty, parental death, and divorce. The research underscores the need for comprehensive policy interventions focusing on improving the living conditions and educational opportunities for street children. Our study contributes to a broader awareness of the socioeconomic challenges faced by street children and offers a framework for policy and practical solutions in Pabna Municipality and similar urban settings.